Design and development of pyramidal microwave absorber using agricultural waste - Nornikman Hassan (School of Computer and Communication Engineering, 2011)
The objective of the research is to develop a low cost microwave absorber using rice husk to meet the microwave range specifications by keeping the best reflection loss performance.